Detrimental effects of rhizobial inoculum early in the life of partridge pea, Chamaecrista fasciculata. Issue 4 (16th May 2018) - Pain, Rachel E.; Shaw, Ruth G.; Sheth, Seema N.
Abstract : Premise of the Study: Mutualistic relationships with microbes may aid plants in overcoming environmental stressors and increase the range of abiotic environments where plants can persist. Rhizobia, nitrogen‐fixing bacteria associated with legumes, often confer fitness benefits to their host plants by increasing access to nitrogen in nitrogen‐limited soils, but effects of rhizobia on host fitness under other stresses, such as drought, remain unclear. Methods: In this greenhouse study, we varied the application of rhizobia ( Bradyrhizobium sp.) inoculum and drought to examine whether the fitness benefits of rhizobia to their host, partridge pea ( Chamaecrista fasciculata ), would differ between drought and well‐watered conditions. Plants were harvested 9 weeks after seeds were sown. Key Results: Young C. fasciculata plants that had been inoculated had lower biomass, leaf relative growth rate, and stem relative growth rate compared to young uninoculated plants in both drought and well‐watered environments. Conclusions: Under the conditions of this study, the rhizobial interaction imposed a net cost to their hosts early in development. Potential reasons for this cost include allocating more carbon to nodule and root development than to aboveground growth and a geographic mismatch between the source populations of host plants and rhizobia. If developing plants incur such costs from rhizobia in nature, they may suffer an early disadvantage relative to other plants, whether conspecifics lacking rhizobia or heterospecifics.